2021
DOI: 10.1039/d1tc01375k
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of B2O3–Bi2O3–ZnO low-temperature glass-ceramics to immobilize iodine-loaded silver-coated silica-gel

Abstract: This study is dedicated to investigating the performance of B2O3-Bi2O3-ZnO low-temperature glass-ceramics to immobilize iodine loaded silver-coated silica-gel (AgIs). Various mass fraction of iodine (15, 20, 25, and 30 wt.%)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The increase of peak intensity at 1000 cm −1 displays that the [BO 4 ] group connected in the form of bridge oxygen increases, which means that the addition of Nd 2 O 3 is conducive to promoting the transformation from [BO 3 ] triangle to [BO 4 ] tetrahedron in the glass network structure, agreeing with the result of Ibrahim reported before 18 . The absorption peaks at 1200 ∼ 1400 cm −1 narrow with the increasement of Nd 2 O 3 , indicating that the content of [BO 3 ] unit with nonbridging oxygen existing in the boron oxygen network descends 18,19 . In conclusion, when the Nd 2 O 3 content is 3 wt%, the content of [BO 4 ] tetrahedron and [BiO 6 ] hexahedron in the glass system is the most, that is, the glass system is strengthened.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The increase of peak intensity at 1000 cm −1 displays that the [BO 4 ] group connected in the form of bridge oxygen increases, which means that the addition of Nd 2 O 3 is conducive to promoting the transformation from [BO 3 ] triangle to [BO 4 ] tetrahedron in the glass network structure, agreeing with the result of Ibrahim reported before 18 . The absorption peaks at 1200 ∼ 1400 cm −1 narrow with the increasement of Nd 2 O 3 , indicating that the content of [BO 3 ] unit with nonbridging oxygen existing in the boron oxygen network descends 18,19 . In conclusion, when the Nd 2 O 3 content is 3 wt%, the content of [BO 4 ] tetrahedron and [BiO 6 ] hexahedron in the glass system is the most, that is, the glass system is strengthened.…”
Section: Resultssupporting
confidence: 87%
“…18 The absorption peaks at 1200 ∼ 1400 cm −1 narrow with the increasement of Nd 2 O 3 , indicating that the content of [BO 3 ] unit with nonbridging oxygen existing in the boron oxygen network descends. 18,19 In conclusion, when the Nd 2 O 3 content is 3 wt%, the content of [BO 4 ] tetrahedron and [BiO 6 ] hexahedron in the glass system is the most, that is, the glass system is strengthened.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The other important and effective measure is to develop a low-temperature matrix. In recent years, the low-temperature glass matrices have been developed and employed to immobilize iodine due to the advantages of low sintering temperature, excellent radiation, and chemical stability. ,, Particularly, glass-bonded iodosodalite waste forms were synthesized at low temperature (650–750 °C), but about 53% iodine was lost during the sintering process . Moreover, Yang et al reported that the iodine waste was successfully immobilized in B–Bi–Zn and Bi–Zn–Si–Al oxide low-temperature glass at 600 °C, while the iodine loss was up to 66 and 79%, respectively.…”
Section: Introductionmentioning
confidence: 99%